The Mechanochemical synthesis of magnesium hydride nanoparticles - Sheppard, Drew; Paskevicius, Mark; Buckley, Craig (Elsevier B.V., 2010)
A mechanochemical method was used to synthesise magnesium hydride nanoparticles with an average crystallite size of 6.7 nm. The use of a reaction buffer was employed as a means of particle size control by restricting agglomeration. Increasing the amount of reaction buffer resulted in a decrease in crystallite size, as determined via X-ray diffraction, and a decrease in particle size, evidenced by transmission electron microscopy.